2022
DOI: 10.21873/invivo.12739
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Rapid Method for Measuring Liver Steatosis Using Bioelectrical Impedance

Abstract: Background/Aim: Easy measurement of liver steatosis without pathological diagnosis may help improve donor surgery efficiency and increase the chances of organ donations. We analyzed the correlations between bioelectrical impedance (BI) in human livers, liver fat content, and pathological findings. Materials and Methods: Sixteen tumor-free liver specimens resected during elective oncological surgery were analyzed. All samples were stored in ice chilled saline before BI measurement. The BI measurement was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The data from the repeated trials for each subject were nonlinearly fitted according to (15). The results of fitting the data from 20 consecutive sets of repeated trials for one of the subjects are shown in Table 4.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…The data from the repeated trials for each subject were nonlinearly fitted according to (15). The results of fitting the data from 20 consecutive sets of repeated trials for one of the subjects are shown in Table 4.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 99%
“…It can be seen that the standard errors are all within 5%, indicating that the estimates of each regression parameter are good. The matrix of characteristic coefficients A for this subject is obtained from (15) as shown in (19): Based on the fitting effects of repeated trials with 60 subjects, it was found that the nonlinear fit of the five-lobe impedance data for a single individual was good, but the characteristic coefficient matrix A obtained from the fitting of different individuals differed significantly. To seek a model for calculating regional lobar ventilation parameters that can be used for different individuals, the individual factor with the greatest degree of influence was introduced to optimize the characteristic coefficient matrix A.…”
Section: Experimental Validation and Results Analysismentioning
confidence: 99%
See 3 more Smart Citations